Take my word for it - Marsden, John, 1950- (Chippendale, Sydney : PAN, 1993)
While writing in a journal for class, Lisa gradually reveals her own personal feelings and concerns, while describing relationships with and problems of other girls at her boarding school.
Keywords: Boarding schools -- Fiction; Diaries -- Fiction; Schools -- Fiction; Australia -- Fiction